The perception of employability skills among Faculty of Administrative Science and Policy Studies (FSPPP) students’ in UiTM Seremban / Ain Fadilah Ismail and Sarah Najihah Jaafar - Ismail, Ain Fadilah; Jaafar, Sarah Najihah (2022)
For this purpose, a survey is conducted with 342 of students Faculty of Administrative Science and Policy Studies (FSPPP) in order to determine the level of employability skills among FSPPP student in UiTM Seremban, the significant differences between perception if employability skills based on gender and examine relationship between career maturity and Online Distance Learning (ODL) towards employability skills. The hypothesis was then proposed and tested using Pearson Correlation. The analysis revealed the majority of the students have a high level of employability skills among FSPPP students in UiTM Seremban because the mean is 3.9755. Next, there are no significant difference values between the perception of employability skills and gender as the p-value 0.716 > 0.05. Lastly, there is positive relationship between the career maturity of students and the influence of the ODL (r = 0.599**, p-value = 0.000, p < 0.05).